Super-sensitive bifunctional nanoprobe: Self-assembly of peptide-driven nanoparticles demonstrating tumor fluorescence imaging and therapy - Han Xiao; Rui Zhang; Xiaobo Fan; Xinglu Jiang; Mingyuan Zou; Xuejiao Yan; Haiping Hao; Guoqiu Wu (Elsevier, 2022)
The development of nanomedicine has recently achieved several breakthroughs in the field of cancer treatment; however, biocompatibility and targeted penetration of these nanomaterials remain as limitations, which lead to serious side effects and significantly narrow the scope of their application. The self-assembly of intermediate filaments with arginine-glycine-aspartate (RGD) peptide (RGD-IFP) was triggered by the hydrophobic cationic molecule 7-amino actinomycin D (7-AAD) to synthesize a bifunctional nanoparticle that could serve as a fluorescent imaging probe to visualize tumor treatment. The designed RGD-IFP peptide possessed the ability to encapsulate 7-AAD molecules through the formation of hydrogen bonds and hydrophobic interactions by a one-step method. This fluorescent nanoprobe with RGD peptide could be targeted for delivery into tumor cells and released in acidic environments such as endosomes/lysosomes, ultimately inducing cytotoxicity by arresting tumor cell cycling with inserted DNA. It is noteworthy that the RGD-IFP/7-AAD nanoprobe tail-vein injection approach demonstrated not only high tumor-targeted imaging potential, but also potent antitumor therapeutic effects in vivo. The proposed strategy may be used in peptide-driven bifunctional nanoparticles for precise imaging and cancer therapy.